+0  
 
0
228
1
avatar

please help I know that the first part is 2 but please need the second part quickly thanks you.

 May 21, 2019
 #1
avatar+111435 
+3

Using the Law of Sines,we have

 

sin (pi/6)/ (3 x)  = sin B / x

 

(1/2) / 3   =   sin B

 

sin B  = (1/6)

 

So    12sin B  =  12 (1/6)  =   2

 

 

C  = pi - A - B

 

C = pi - pi/6 - arcsin (1/6)

 

C = 5pi/6 - arcsin(1/6)

 

sin C  =  sin (5pi/6 - arcsin (1/6) )    =  sin (A - B)  =  sinAcosB - sin B cos A

 

sin C  =   (1/2)sqrt(35)/6 -  (1/6)(-sqrt(3)/2)

 

sin C  =[  sqrt (35) +sqrt(3)] / 12

 

So

 

12 sin C    =    12  [ sqrt(35) + sqrt(3) ] / 12  =     [ sqrt(35) + sqrt(3) ]

 

 

cool cool cool

 May 22, 2019

12 Online Users

avatar
avatar